Inside Cover: A Bioorthogonal Raman Reporter Strategy for SERS Detection of Glycans on Live Cells (Angew. Chem. Int. Ed. 28/2013). Issue 28 (5th June 2013) - Lin, Liang; Tian, Xiangdong; Hong, Senlian; Dai, Peng; You, Qiancheng; Wang, Ruyi; Feng, Lianshun; Xie, Can; Tian, Zhong‐Qun; Chen, Xing
<x xml:space="preserve">Abstract</x> Raman detection of glycans on surfaces of live cells has been achieved, as described in the Communication by Z.‐Q. Tian, X. Chen, and co‐workers on page 7266 ff. A bioorthogonal Raman reporter (for alkyne, azide, and nitrile groups, or carbon–deuterium bonds) was installed onto the monosaccharide analogues, which were metabolically incorporated into cell surface glycans. The Raman reporter is detected using surface‐enhanced Raman scattering with the aid of gold nanoparticles.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>